Liquid-Phase Mass Transfer in Fixed and Fluidized Beds of Large Particles - Upadhyay S.N.; Tripathi G. (My University, 2025)
Liquid-phase mass-transfer coefficients from fixed and fluidized beds of cylindrical and modified cylindrical pellets of benzoic acid are measured in the NRe″ range of 0.405-11,610. Correlations are proposed for the entire liquid-solid range. © 1975, American Chemical Society. All rights reserved.